THE CORRELATION OF INTERPREGNANCY INTERVAL AND TEENAGE PREGNANCY WITH STUNTING INCIDENCE IN PUSKESMAS HARAPAN BARU SAMARINDA - Rini Ernawati (Journal of Midwifery and Reproduction, 2021)
Abstract Stunting is a chronic problem that occurs in children that causes growth problems which is short stature. Long-term impact on stunted children is cognitive impairment, learning difficulties and a high risk of developing degenerative diseases. Stunting in East Kalimantan province is quite high, increasing each year, from 26.7% in 2015, to 30.6% in 2017, and in Samarinda city by 28.8%. This study aims to determine the relationship between interpregnancy interval and teenage pregnancy with stunting. This research used survey method and quantitative research type with cross sectional approach. The sample were mothers who have toddlers (1-5 years), as many as 70 respondents, Questionnaire was used as instrument. Statistical analysis used was Chi-square. The results of the study showed analysis between interpregnancy interval and the incidence of stunting showed p-value of 0.0004 <0.05, so that H0 is rejected, meaning that there is a relationship between interpregnancy interval with stunting, and teenage pregnancy with stunting incidence showed p value of 0.000 <0.05, so that H0 is rejected, which means that there is a relationship between teenage pregnancy and stunting at Puskesmas Harapan Baru Samarinda Seberang. There needs to be a program to increase teenagers knowledge about women's health and pregnancy.